Finance for low-emission food systems: For the CGIAR Research Initiative on Low-Emission Food Systems - Wattel, Cor; Negede, Betelhem; Desczka, Sabine; Pamuk, Haki; Asseldonk, Marcel van (Wageningen University & Research, 2023)
The objective of this note is to map the global finance landscape that is relevant to the CGIAR Research Initiative on Low-Emission Food Systems (the Project). The note is part of the initial research phase of the project’s work stream on financial instruments as a tool for scaling of measures for achieving lower emissions in food systems (WP4). The objective of this research phase is to develop a typology of most adopted financial instruments for low-emission investments.